2015
DOI: 10.18325/jkmr.2015.25.4.175
|View full text |Cite
|
Sign up to set email alerts
|

The Case Report of Anaphylaxis after Treated with Bee-Venom Acupuncture

Abstract: The purpose of this study was to report an anaphylaxis after treated with Bee-venom acupuncture. Anaphylaxis is a clinical syndrome characterized by the acute system reaction of multiple organ systems to an IgE-mediated immunologic mediator release in previously sensitized individuals. We investigated the patients who had injected with Bee-venom in our clinic from March 2, 2014 to May 30, 2015. and two patients of anaphylaxis treated by Bee-Venom acupuncture were observed. One case of anaphylaxis was expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…Meanwhile, one retrospective case study reported that the mean time to onset of anaphylaxis after BV therapy was 21.75 min [111], therefore, it is necessary to monitor the patient for at least 30 min after BV treatment. One recent study reported that high levels of basal serum tryptase increased the risk of severe anaxphylaxis [110]. As per this information, even if an injection of BV did not cause anaphylaxis in the past, if the basal serum tryptase is elevated at a certain time for some reason, anaphylaxis may occur when BV is injected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meanwhile, one retrospective case study reported that the mean time to onset of anaphylaxis after BV therapy was 21.75 min [111], therefore, it is necessary to monitor the patient for at least 30 min after BV treatment. One recent study reported that high levels of basal serum tryptase increased the risk of severe anaxphylaxis [110]. As per this information, even if an injection of BV did not cause anaphylaxis in the past, if the basal serum tryptase is elevated at a certain time for some reason, anaphylaxis may occur when BV is injected.…”
Section: Discussionmentioning
confidence: 98%
“…In clinics, a skin test is used to determine whether BV treatment is suitable for individual patients, however, negative results of a skin test do not always guarantee safety [109]. Furthermore, one case report showed that anaphylaxis may occur in patients who have had no adverse reaction after former BV therapy [110]. Since anaphylaxis can occur under any circumstances, an emergency kit in accordance with the guidelines for management of anaphylaxis should always be kept ready.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BVP therapy is relatively safe. However, since cases of moderate to greater AEs have been reported after multiple exposures to BVP [ 19 ], continuous monitoring is required if repeated BVP is needed.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Previous studies have focused on anaphylactic reactions; however, there are few studies on the characteristics of patients treated in an emergency department (ED) after bee stings. 7 8 9…”
Section: Introductionmentioning
confidence: 99%